Improvements and characterization of a microcosmic-based device for sediment erosion - Shao, Yuyang; Zhang, Zhongao; Tang, Yulin; Zhang, Wei; Maa, Jerome P. -Y. (Frontiers in Marine Science, 2024)
Effective management of sediment transport in water bodies is crucial for maintaining navigational channels and reducing siltation in harbors. This study introduces the first effort in the development of a Field Instrument for Measuring Bed Erosion Response based on microcosmic analysis. The device is designed to automatically measure the sediment bed responses under a series of selected bed shear stresses to determine the critical bed shear stresses for sediment incipient motion and the erosion rates for selected excess bed shear stresses. Numerical simulations were conducted using computational fluid dynamics software (FLUENT) to ensure a reasonable and uniform distribution of the selected bed shear stress across the sediment bed. A lab version of this device was also built and tested using granular sandy sediments and the results were validated against the Shields curve for incipient motion. During this test, however, a problem of sandy bed liquefaction at the bed center was identified because of the pumping out of water at top center. For enhancing the device performances, modifications of the pumping intake were made to eliminate the liquefaction problem. Further a lab test on kaolinite beds with three consolidated durations also demonstrated the capability of this improved device. The study confirms the basic design parameters of the improved device, including the optimal rotating speeds of its pump and disk motors, which are critical for achieving the desired erosion dynamics. These results highlight the potential of the device to significantly improve the precision and efficiency of sediment transport studies in natural aquatic environments.